Speciation in protists: Spatial and ecological divergence processes cause rapid species diversification in a freshwater chrysophyte - Škaloud, Pavel; Škaloudová, Magda; Doskočilová, Pavla; Kim, Jong Im; Shin, Woonghi; Dvořák, Petr (Molecular ecology, 2019)
Although eukaryotic microorganisms are extremely numerous, diverse and essential to global ecosystem functioning, they are largely understudied by evolutionary biologists compared to multicellular macroscopic organisms. In particular, very little is known about the speciation mechanisms which may give rise to the diversity of microscopic eukaryotes. It was postulated that the enormous population sizes and ubiquitous distribution of these organisms could lead to a lack of population differentiation and therefore very low speciation rates. However, such assumptions have traditionally been based on morphospecies, which may not accurately reflect the true diversity, missing cryptic taxa. In this study, we aim to articulate the major diversification mechanisms leading to the contemporary molecular diversity by using a colonial freshwater flagellate, Synura sphagnicola, as an example. Phylogenetic analysis of five sequenced loci showed that S. sphagnicola differentiated into two morphologically distinct lineages approximately 15.4 million years ago, which further diverged into several evolutionarily recent haplotypes during the late Pleistocene. The most recent haplotypes are ecologically and biogeographically much more differentiated than the old lineages, presumably because of their persistent differentiation after the allopatric speciation events. Our study shows that in microbial eukaryotes, species diversification via the colonization of new geographical regions or ecological resources occurs much more readily than was previously thought. Consequently, divergence times of microorganisms in some lineages may be equivalent to the estimated times of speciation in plants and animals.
Keywords: Haplotypes; DNA, Mitochondrial; pleistocene; Genetic Speciation; vznik druhů (genetika); Chrysophyta; Chrysophyceae; protists; speciation; Ecosystem; biologická evoluce; haplotypy; biogeography; Fresh Water; Species Specificity; fylogeneze; druhová specificita; taxonomy; ekosystém; Sequence Analysis, DNA; biodiverzita; sladká voda; sekvenční analýza DNA; mitochondriální DNA; Biological Evolution; Phylogeny; Biodiversity; chrysophyceae